Giant Cell Tumor of the Capitate and Hamate: Case Report and of Literature Review - Abdusamad, V.; Singh, Vivek; Jain, Rohit; Singh, Divya (Journal of Wrist Surgery, 2020)
Background In the hand, giant cell tumors (GCTs) of the bones account for 2 to 5% of all hand tumors; they are often seen in the metacarpals and phalanges, seldom in the carpal bones. In the carpal bones, GCT usually occurs as a single lesion, with multifocal involvement being extremely rare. On analysis of recent English literature, we could find out only two reports having simultaneous involvement of multiple carpal bones.Case Description We report a case of a 29-year-old female with simultaneous involvement of two carpal bones: capitate and hamate. After confirming the diagnosis by histopathological examination, the affected carpals were resected, and the defect was filled with autologous bone graft. Follow-up at 18 months demonstrated no evidence of local recurrence or metastatic disease, and the patient is now having a reasonable hand function.Literature Review We analyzed nine case reports on GCTs in carpal bones in the past 25 years. Seven out of nine cases that we could analyze showed single carpal bone involvement (three capitate, two scaphoid, one hamate, one triquetrum). In these, four patients had undergone resection, and five patients had undergone curettage, of whom one patient came back 5 months later with recurrence. Only two cases were there with simultaneous involvement of multiple carpal bones. Both the cases were managed with resection and reconstruction with autologous graft iliac graft.Clinical Relevance GCTs of the carpal bones are relatively rare, and simultaneous involvement of two bones is rarer. Every attempt should be made to preserve useful wrist range of motion by excision and limited carpal fusion.
Keywords: giant cell tumor; capitate and hamate; carpal fusion; tricortical iliac graft